Pore formation by the CDTb component of the Clostridioides difficile binary toxin is Ca2+-dependent - Dinendra L. Abeyawardhane; Spiridon E. Sevdalis; Kaylin A. Adipietro; Raquel Godoy-Ruiz; Kristen M. Varney; Izza F. Nawaz; Alejandro X. Spittel; Daniel Hunter; Richard R. Rustandi; Vitalii I. Silin; Amedee des Georges; Mary E. Cook; et al. (Communications Biology)
Abstract Clostridioides difficile infection (CDI) is one of the five most urgent bacterial threats in the United States. Furthermore, hypervirulent CDI strains express a third toxin termed the C. difficile binary toxin (CDT), and its molecular mechanism for entering host cells is not fully elucidated. Like other AB-type binary toxins, CDT enters host cells via endosomes. Here we show via surface plasmon resonance and electrochemical impedance spectroscopy that the cell-binding component of CDT, termed CDTb, binds and form pores in lipid bilayers in the absence of its enzymatic component, CDTa. This occurs upon lowering free Ca2+ ion concentration, and not by decreasing pH, as found for other binary toxins (i.e., anthrax). Cryogenic electron microscopy (CryoEM), X-ray crystallography, and nuclear magnetic resonance (NMR) studies show that dissociation of Ca2+ from a single site in receptor binding domain 1 (RBD1) of CDTb triggers conformational exchange in CDTb. These and structure/function studies of a Ca2+-binding double mutant targeting RBD1 (i.e., D623A/D734A) support a model in which dissociation of Ca2+ from RBD1 induces dynamic properties in CDTb that enable it to bind and form pores in lipid bilayers.